1994
DOI: 10.1159/000262019
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Various Calcium Fluoride Preparations in Inorganic Solutions and in Stimulated Human Saliva

Abstract: The aim of the present study was to examine the dissolution of various preparations of calcium fluoride in inorganic solutions and in human saliva. Calcium fluoride was prepared by mixing either 0.25 or 0.02 mol/l calcium chloride with 0.5 or 0.04mol/l sodium fluoride. After preparation, the salts were washed in 1 mmol/l calcium chloride solution and in distilled water. A commercial product, calcium fluoride Suprapur® (Merck), was used for comparison. The solubility of the salts was examined in distilled water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
3
15
0
2
Order By: Relevance
“…From a chemical point of view, the drinks are poorly defined and unsuited for such studies. Further, we have not used high quality commercial analytical grade calcium fluoride because this salt behaves differently from the low-quality salts that are formed in the oral cavity as a result of topical treatments [Larsen and Ravnholt, 1994]. Generally, after the equilibration with calcium fluoride the drinks were slightly undersaturated with respect to the salt (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…From a chemical point of view, the drinks are poorly defined and unsuited for such studies. Further, we have not used high quality commercial analytical grade calcium fluoride because this salt behaves differently from the low-quality salts that are formed in the oral cavity as a result of topical treatments [Larsen and Ravnholt, 1994]. Generally, after the equilibration with calcium fluoride the drinks were slightly undersaturated with respect to the salt (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of plaque cancelled a significant source of ions to heal the erosive insult, and this may be a reasonable explanation as to why clarified saliva was associated with a more severe impact on hardness readings. Since centrifugation eliminated solids in suspension, clarified saliva lacked those components of plaque, and fragments of plaque itself, that acted as reservoirs of minerals and fluorides that protected from erosion and/or repaired in situ erosion damage [Jenkins and Ferguson, 1966;Larsen and Ravnholt, 1994;Sorvari et al, 1994]. Featherstone et al [1993] looked at the actual fractions of saliva, endeavouring to accurately establish the protective role of each combination, but found that no specific protein or group of proteins on their own could account for the results observed in whole and dialysed saliva assays.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, Coca-Cola ® , Schweppes ® Dry Grape, 7Up ® and an orange juice (Arla ® ) were included as wellknown references. Solid calcium fluoride was produced by slowly mixing equal volumes of 0.25 mol/l CaCl 2 and 0.5 mol/l NaF [Larsen and Ravnholt, 1994]. The salt was aged for 24 h and washed twice in distilled water before drying.…”
Section: Methodsmentioning
confidence: 99%